PERANCANGAN SISTEM INFORMASI AKUNTANSI PENGELOLAAN DATA TRANSAKSI PADA BENGKEL SIBOLGA MOTOR MEDAN - Nada Ria Hasibuan; Marlyna Infryanty Hutapea; Gortap Lumbantoruan (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2022)
Sibolga Motor Medan is an individual owned workshop business engaged in repair services and the sale of motorbike spare parts, the business activities are still manual systems and have not used a computer system. To improve the performance of the motorbike workshop, a motorbike workshop data management information system will be designed using a design based on Microsoft Visual Basic.Net 2010. The system built will be able to produce customer data information, service data, spare parts inventory data, service transaction management data and parts sales. motorbike repair shop spare parts can also make reports easier and more efficient, provide accurate, relevant, timely information and can facilitate computerized transactions from consumers to the repair shop. Collection of the requirements needed in designing the information system at the Sibolga Motor workshop by the author through interviews and observations. Furthermore, the author will design a system related to the design of a motorbike workshop data processing information system using database and interface design. Keywords: Information Systems, Data Processing, Transactions.